'We Don't Have the Same Opportunities as Others': Shining Bourdieu's Lens on UK Roma Migrants' Precarious (Workers') Habitus. (April 2022) - Harrison, Patricia; Collins, Helen; Bahor, Alexandra
According to a 2019 UK government report, Roma had the 'worst employment outcomes' of any ethnic group in the UK with similar evidence in Europe. Roma are in the growing flexible, mobile workforce that constitute precarious, insecure workers. Based on a qualitative in-depth study of these precarious workers, and utilising Bourdieu's concepts, we show the impact of flexploitation, while sharing Roma's habitus and capitals that distinguish and challenge the dominant homogenous narrative about the response to precarity. We argue that Roma, owing to their long-standing, symbiotic relationship with precarity, compounded by centuries-old persecution, offer insights into the lived experience of precarious workers. While not diminishing the impact of flexploitation, we culminate with our claim that Roma possess a precarious habitus and, as such, are a 'fish in water' with a distinguishing feature of 'social capital on the move'.